The technology of video and audio streaming - Austerberry, David (Focal Press, 2005)
* Learn the end-to-end process, starting with capture from a video or audio source through to the consumer's media player* A quick-start quide to streaming media technologies* How to monetize content and protect revenue with digital rights managementFor broadcasters, web developers, project managers implementing streaming media systems, David Austerberry shows how to deploy the technology on your site, from video and audio capture through to the consumer's media player. The book first deals with Int.